Characterizing Asymmetric Collaborative Interactions in Virtual and Augmented Realities - Grandi, Jeronimo Gustavo; Galvan Debarba, Henrique; Maciel, Anderson (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
We present an assessment of asymmetric interactions in Collaborative Virtual Environments (CVEs). In our asymmetric setup, two co-located users interact with virtual 3D objects, one in immersive Virtual Reality (VR) and the other in mobile Augmented Reality (AR). We conducted a study with 36 participants to evaluate performance and collaboration aspects of pair work, and compare it with two symmetric scenarios, either with both users in immersive VR or mobile AR. To perform this experiment, we adopt a collaborative AR manipulation technique from literature and develop and evaluate a VR manipulation technique of our own. Our results indicate that pairs in asymmetric VR-AR achieved significantly better performance than the AR symmetric condition, and similar performance to VR symmetric. Regardless of the condition, pairs had similar work participation indicating a high cooperation level even when there is a visualization and interaction asymmetry between the participants.